Comparison of electrophysiological left bundle branch pacing characteristics in different bilateral electrode pacing vector configurations - Wu, Hao; Jiang, Longfu; Shen, Jiabo; Zhang, Lu (Frontiers in Cardiovascular Medicine, 2025)
IntroductionLeft bundle branch pacing (LBBP) in bipolar pacing with anodal capture produces a more balanced ventricular activation than conventional unipolar pacing but need high pacing output. The present study aimed to compare the electrophysiological characteristics of LBBP in different bilateral electrode pacing vector configurations.MethodsA total of 57 patients who met the criteria for left bundle branch (LBB) capture and underwent three bilateral electrode pacing vector configuration test were enrolled. The electrocardiogram (ECG) and electrogram (EGM) parameters were evaluated and other electrophysiological characteristics were analyzed using a three-electrode configuration test.ResultsSeven capture modes [right ventricular septal (RVS) + left ventricular septal (LVS) + LBB, RVS + LBB, LVS + LBB, RVS + LVS, RVS, LVS, and LBB] were utilized in the study. The thresholds of full fusion mode (RVS + LVS + LB) in Bilateral Cathodes and Ring Bipolar were all lower than that in Tip Bipolar (1.2 ± 0.5 V vs. 2.7 ± 1.0 V, P < 0.001; 1.6 ± 0.6 V vs. 2.7 ± 1.0 V, P < 0.001). Full fusion mode had the shortest P-QRS (116.9 ± 12.8 ms) and V1 RWPT (94.5 ± 12.3 ms), V6 RWPT remain the shortest (64.9 ± 9.7 ms).ConclusionChanging the bilateral electrode pacing vector configuration to Bilateral Cathodes and Ring Bipolar can reduce the full fusion mode capture threshold compared to conventional bipolar pacing.